Abstracts of Philippine researches in home economics, 1923-1978 - Domingo, Generosa T. (1981)
The study aims to compile into a single volume abstracts of all available bachelor's and master's theses, special problems, seminar papers and doctoral dissertations in home economics which have been completed and submitted to degree-granting institutions of the United States and the Philippines for the period 1923-1978.